2019
DOI: 10.1111/bph.14623
|View full text |Cite
|
Sign up to set email alerts
|

Trehalose as a promising therapeutic candidate for the treatment of Parkinson's disease

Abstract: Parkinson's disease (PD) is a progressive movement disorder resulting primarily from loss of nigrostriatal dopaminergic neurons. PD is characterized by the accumulation of protein aggregates, and evidence suggests that aberrant protein deposition in dopaminergic neurons could be related to the dysregulation of the lysosomal autophagy pathway. The therapeutic potential of autophagy modulators has been reported in experimental models of PD. Trehalose is a natural disaccharide that has been considered as a new ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 151 publications
(239 reference statements)
3
48
0
1
Order By: Relevance
“…Tre is an inducer of autophagy-lysosomal biogenesis by an unclear mechanism. It has demonstrated anti-inflammatory effects in many diseases [34][35][36]. In this study, Tre induced TFEB nuclear localization and upregulated TFEB expression in the lungs (Figure 4A-C) and AMs ( Figure 4D-E) of CS-treated mice.…”
Section: Tre Activates Tfeb and Affects Autophagy-associated Proteinssupporting
confidence: 52%
“…Tre is an inducer of autophagy-lysosomal biogenesis by an unclear mechanism. It has demonstrated anti-inflammatory effects in many diseases [34][35][36]. In this study, Tre induced TFEB nuclear localization and upregulated TFEB expression in the lungs (Figure 4A-C) and AMs ( Figure 4D-E) of CS-treated mice.…”
Section: Tre Activates Tfeb and Affects Autophagy-associated Proteinssupporting
confidence: 52%
“…13,35 Moreover, Tre is a natural disaccharide that has been considered as a new candidate in the therapy of neurodegenerative diseases. 36 As expected, Tre has a protective effect on Mn-induced mitochondrial and neurocyte damage. Our data showed that Tre pre-treatment could effectively ameliorate the loss of ΔΨm, ATP depletion and cell apoptosis.…”
Section: F I G U R E 6 Effects Of Mn Andsupporting
confidence: 59%
“…Tre has multiple biological functions, including anti‐inflammation, induction of autophagy, alleviation of oxidative stress and mitigation of ER stress . Moreover, Tre is a natural disaccharide that has been considered as a new candidate in the therapy of neurodegenerative diseases . As expected, Tre has a protective effect on Mn‐induced mitochondrial and neurocyte damage.…”
Section: Discussionmentioning
confidence: 81%
“…It is noteworthy that despite the presence of trehalase in the gut, orally administered trehalose has been proven to exert significant biological effects in mouse models of many different diseases, such as Parkinson's, Alzheimer's, muscular dystrophy, Huntington's disease, ALS, prion's disease, OPMD, obesity, hepatic steatosis, diabetes, or chronic ischemia [35,53,54]. Thus, we cannot exclude that trehalose effects might occur, or at least count with contribution of indirect effects in peripheral energy metabolism and inflammatory pathways [55,56].…”
Section: Discussionmentioning
confidence: 99%